17m
Because horizontal distance is 8m, vertical distance is 15m
So distance between A and Enid square root of 8^2+15^2
<h2>
Answer:</h2>
![\left(\frac{4^{21}}{5^6}\right)](https://tex.z-dn.net/?f=%5Cleft%28%5Cfrac%7B4%5E%7B21%7D%7D%7B5%5E6%7D%5Cright%29)
or
4 to the 21st over 5 to the 6th.
<h2>
Step-by-step explanation:</h2>
First, we need to write our expression. Let's do it step by step:
<u>4 to the 7th:</u>
![4^7](https://tex.z-dn.net/?f=4%5E7)
<u>5 squared:</u>
![5^2](https://tex.z-dn.net/?f=5%5E2)
<u>4 to the 7th over 5 squared:</u>
![\frac{4^7}{5^2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%5E7%7D%7B5%5E2%7D)
<u>4 to the 7th over 5 squared all raised to the 3rd power:</u>
<u>
</u>
Using the law of exponents:
![\left(\frac{4^{7\times 3}}{5^{2\times 3}}\right) \\ \\ \left(\frac{4^{21}}{5^6}\right)](https://tex.z-dn.net/?f=%5Cleft%28%5Cfrac%7B4%5E%7B7%5Ctimes%203%7D%7D%7B5%5E%7B2%5Ctimes%203%7D%7D%5Cright%29%20%5C%5C%20%5C%5C%20%5Cleft%28%5Cfrac%7B4%5E%7B21%7D%7D%7B5%5E6%7D%5Cright%29)
Finally, the answer is 4 to the 21st over 5 to the 6th.
Answer:
y = 13 - 4x
Why?
4y +y = 13
Subtract 4x from both sides
4x+y-4x = 13 - 4x
Simplify
Y= 13 - 4x
Have a good day
Answer:
![4 \sqrt{6} \times \sqrt{3} = 12 \sqrt{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%2012%20%5Csqrt%7B2%7D%20)
Step-by-step explanation:
We want to simplify the radical expression:
![4 \sqrt{6} \times \sqrt{3}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20)
We write √6 as √(2*3).
This implies that:
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2 \times 3} \times \sqrt{3}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%20%5Ctimes%203%7D%20%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20)
We now split the radical for √(2*3) to get:
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2} \times \sqrt{3} \times \sqrt{3}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20)
We obtain a perfect square at the far right.
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2} \times (\sqrt{3} )^{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%7D%20%20%5Ctimes%20%20%28%5Csqrt%7B3%7D%20%29%5E%7B2%7D%20)
This simplifies to
![4 \sqrt{6} \times \sqrt{3} = 4 \sqrt{2} \times 3](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Csqrt%7B2%7D%20%20%5Ctimes%203)
This gives us:
![4 \sqrt{6} \times \sqrt{3} = 4 \times 3 \sqrt{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%204%20%5Ctimes%203%20%5Csqrt%7B2%7D%20)
and finally, we have:
![4 \sqrt{6} \times \sqrt{3} = 12 \sqrt{2}](https://tex.z-dn.net/?f=4%20%5Csqrt%7B6%7D%20%20%5Ctimes%20%20%5Csqrt%7B3%7D%20%20%3D%2012%20%5Csqrt%7B2%7D%20)
Answer:
Step-by-step explanation:it’s number 4